West African Economic and Monetary Union : Common Policies of Member Countries-Press Release; Staff Report; and Statement by the Executive Director for West African Economic and Monetary Union. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments, outlook, and risks of West African Economic and Monetary Union (WAEMU). Despite the fragile security situation in some member countries and a less favorable external environment in 2015, economic growth exceeded 6 percent for the second consecutive year, driven by ongoing infrastructure investments, solid private consumption, and favorable agricultural campaigns. This paper also discusses how timely and effective implementation of the planned policies is required at the national level to maintain the growth momentum while preserving external stability and debt sustainability and to enact the planned regulatory reforms and improve further supervisory processes and the enforcement of existing prudential norms.